LOCAL LANGUAGE AS A MEANS - Katharina Rustipa (Universitas Stikubank (UNISBANK) Semarang, 2013)
Indonesia is a large nation in terms ofgeography, population, ethnics, cultures, and vernaculars. Indonesian 1945constitution guarantees that the ethnics, cultures, vernaculars in Indonesiawill be taken care of by the government. But in reality, speakers of manyvernaculars in Indonesia are getting less and less. Sneddon states that this iscaused by lingua franca and language shift (2003: 203). Vernaculars will bepreserved if they are respected, used, and inherited to the followinggeneration. And maintaining them will lead the unity in diversity. Friberg(2011) states that languages that can be maintained are the ones written andcan be read. We should not only use our national language, but also ourvernaculars in order to maintain our regional languages, our native localidentity. And as people of multilingual community, it is better if we aremultilingual. For example: Indians are used to speaking five up to sixlanguages, based on the languages spoken by people around them. It should beborne in mind that vernaculars reflect local cultures, local values, local identity.The exposure to regional languages will make people familiar with thelanguages. And as a result, the people will be familiar with their own culturalvalues and other people’s cultural values. Komorowska (2010) claims thatunderstanding others’ languages will promote intercultural competence,understanding and communication between citizens. And this will lead to peaceprocess, to deeper knowledge of other communities and their cultures, and inconsequence to promote tolerance. Key words: Vernaculars,language maintenance, language shift, lingua franca, peace, tolerance,multilingual, multicultural, cultural values, inter-cultural understanding,inter-cultural competence, endangered language, language decay